Perancangan dan Pengembangan Aplikasi Inventory Produk UMKM Berbasis Web - Aziza Nurul Amanah; Muchlis Muchlis (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2026)
Inventory management is a crucial aspect of business sustainability, particularly for Micro, Small, and Medium Enterprises (MSMEs) that often face limitations in data management and technological adoption. Selaras Muba Lestari is Incubation Center, which supports MSMEs in Musi Banyuasin Regency, encounters challenges in managing product inventory due to reliance on manual recording systems. This study aims to design and develop a web-based inventory application using the Laravel framework to improve the efficiency and accuracy of stock management. The research adopts the Software Development Life Cycle (SDLC) Waterfall model, which includes requirements analysis, system design, implementation, and testing. The results indicate that the developed system is capable of improving data accuracy, accelerating the recording process, and providing real-time inventory reports. Furthermore, this study reinforces previous findings that digitalizing inventory systems serves as a strategic solution to enhance the competitiveness of MSMEs.